Design a compact square ring patch antenna with AMC for SAR reduction in WBAN applications - Abdul Rashid Omar Mumin; R. Alias; Jiwa Abdullah; Samsul Haimi Dahlan; Jawad Ali; Sanjoy Kumar Debnath (Institute of Advanced Engineering and Science, 2020)
In this paper presents a compact square ring patch antenna with miniaturized AMC structure at 5.8 GHz for WBAN applications. To minimize detuning, keeping its radiation efficiency high and acceptable gain while keeping the SAR levels low for safety is a challenging task. One of the critical issues in WBAN antenna design is the size of the antenna for portable devices, because the size affects the gain and bandwidth. The AMC configuration decreases the back radiation and the effect frequency detuning results from the high loss in the human body. Furthermore, the AMC also increases the front-to-back ratio (FBR) of 15.3 dB. The proposed antenna has dimensions of 15.27×15.27×2.2 mm3 and provides a 404 MHz impedance bandwidth, with a gain improvement of 8.69 dBi and a 93.7% reduction of the initial SAR value. For this reason, the antenna is suitable for WBAN application in various fields, particularly in medical technology.